2009
DOI: 10.1002/ejoc.200800929
|View full text |Cite
|
Sign up to set email alerts
|

New Route to the Synthesis of the Isocryptolepine Alkaloid and Its Related Skeletons Using a Modified Pictet–Spengler Reaction

Abstract: A new route to the synthesis of the isocryptolepine alkaloid with antimalarial activity using a modified Pictet-Spengler reaction has been devised. The strategy was then used to generate libraries based on three structural variants of the alkaloid. Compounds based on these three variants in general were accessed in three steps through a modified PictetSpengler cyclization reaction as the key step. The C-2-, C-3-, or N-1-linked (aminoaryl)indoles (8, 12, 13) required for cyclization were obtained by treating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 91 publications
(27 reference statements)
1
45
0
Order By: Relevance
“…Although Kundu and coauthors have reported the synthesis of indolo [1,2-a]quinoxalines in situ via the intermediates, 5,6-dihydro-indolo[1,2-a]quinoxalines, excess amounts (1.5 equiv.) of trifluoroacetic acid (TFA), a strong Brønsted acid, were required to prepare 5,6-dihydro-indolo[1,2-a]quinoxalines by the PicteteSpengler reaction [23]. Consequently, the development of environmentally friendly and less expensive catalysts for the construction of a library of 5,6-dihydro-indolo[1,2-a]quinoxalines is very important.…”
Section: Chemistrymentioning
confidence: 99%
“…Although Kundu and coauthors have reported the synthesis of indolo [1,2-a]quinoxalines in situ via the intermediates, 5,6-dihydro-indolo[1,2-a]quinoxalines, excess amounts (1.5 equiv.) of trifluoroacetic acid (TFA), a strong Brønsted acid, were required to prepare 5,6-dihydro-indolo[1,2-a]quinoxalines by the PicteteSpengler reaction [23]. Consequently, the development of environmentally friendly and less expensive catalysts for the construction of a library of 5,6-dihydro-indolo[1,2-a]quinoxalines is very important.…”
Section: Chemistrymentioning
confidence: 99%
“…of o-iodonitrobenzene in dioxane at 100 8C using K 2 CO 3 as the base (Scheme 124). [162] As shown in Scheme 124, compounds 232a-c were then used as precursors to 7H-indoloA C H T U N G T R E N N U N G [2,3-c]quinolines 233. [162] In 2010, a versatile catalyst system based on PdA C H T U N G T R E N N U N G (OAc) 2 /bis(diphenylphosphino)methane (dppm) that works "on water" giving site selective arylation of free NH-indoles with aryl halides was developed by Djakovitch and co-workers.…”
Section: P(o)h Was Employed As the Prea C H T U N G T R E N N U N G Lmentioning
confidence: 99%
“…[162] As shown in Scheme 124, compounds 232a-c were then used as precursors to 7H-indoloA C H T U N G T R E N N U N G [2,3-c]quinolines 233. [162] In 2010, a versatile catalyst system based on PdA C H T U N G T R E N N U N G (OAc) 2 /bis(diphenylphosphino)methane (dppm) that works "on water" giving site selective arylation of free NH-indoles with aryl halides was developed by Djakovitch and co-workers. [163] The control of the site-selectivity was achieved by small changes in the base/halide partners so that both C-2 and C-3 arylylated 1H-indoles could be obtained.…”
Section: P(o)h Was Employed As the Prea C H T U N G T R E N N U N G Lmentioning
confidence: 99%
“…They show wide applications as anti-malarial [2], anti-microbial [4,5], anti-imflammatory [6], and anticancer agents [7]. Cryptolepines are also known to bind tightly to DNA and behave as typical intercalating agents [8][9][10]. Considerable interest has been shown to the anti-plasmodial indoloquinolines and attempts have been made to synthesize similar isomers to compare their biological activities with the naturally occurring isomers [11].…”
Section: Introductionmentioning
confidence: 99%